2021
DOI: 10.1002/adfm.202107062
|View full text |Cite
|
Sign up to set email alerts
|

A Shape‐Variable, Low‐Temperature Liquid Metal–Conductive Polymer Aqueous Secondary Battery

Abstract: A shape-variable aqueous secondary battery operating at low temperature is developed using Ga 68 In 22 Sn 10 (wt%) as a liquid metal anode and a conductive polymer (polyaniline (PANI)) cathode. In the GaInSn alloy anode, Ga is the active component, while Sn and In increase the acid resistance and decrease the eutectic point to -19 °C. This enables the use of strongly acidic aqueous electrolytes (here, pH 0.9), thereby improving the activity and stability of the PANI cathode. Consequently, the battery exhibits … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Although the resistances of the two cells gradually increased with cycling, the semicircles in the high‐medium frequency region of the Zn@ZnP‐NC//MnO 2 cell were smaller than that of the Zn//MnO 2 cell, which indicated that the Zn@ZnP‐NC//MnO 2 had lower SEI film resistance and charge transfer resistance at the electrode and electrolyte interface. [ 1 , 31 ] Meanwhile, the relationship of Z ′ versus ω –1/2 in the low‐frequency region is shown in Figure S25c,d of Supporting Information. At either the 10th or the 100th cycle, the Zn@ZnP‐NC//MnO 2 cell represented lower slopes than the Zn//MnO 2 cell, which indicated its excellent Zn‐ion kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…Although the resistances of the two cells gradually increased with cycling, the semicircles in the high‐medium frequency region of the Zn@ZnP‐NC//MnO 2 cell were smaller than that of the Zn//MnO 2 cell, which indicated that the Zn@ZnP‐NC//MnO 2 had lower SEI film resistance and charge transfer resistance at the electrode and electrolyte interface. [ 1 , 31 ] Meanwhile, the relationship of Z ′ versus ω –1/2 in the low‐frequency region is shown in Figure S25c,d of Supporting Information. At either the 10th or the 100th cycle, the Zn@ZnP‐NC//MnO 2 cell represented lower slopes than the Zn//MnO 2 cell, which indicated its excellent Zn‐ion kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…The XPS spectra of Sn 3d in Figure c for SFO@C-IV and Figure S9a–d for others show two main peaks at ∼487.1 and ∼495.5 eV, corresponding to Sn 3d 5/2 and Sn 3d 3/2 , mainly due to the existence of Sn­(II). Meanwhile, the Sn 3d XPS peaks of SFO@C-III in Figure S9d can be deconvoluted as 486.62, 485.95, and 484.41 eV of Sn 3d 5/2 for Sn 4+ , Sn 2+ , and Sn 0 , respectively, and 495.15, 494.50, and 493.10 eV of Sn 3d 3/2 for Sn 4+ , Sn 2+ , and Sn 0 , respectively, indicating metallic Sn existing in SFO@C-III Figure d shows the C 1s XPS spectrum of SFO@C-IV; other samples are shown in Figure S10.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Meanwhile, the Sn 3d XPS peaks of SFO@ C-III in Figure S9d can be deconvoluted as 486.62, 485.95, and 484.41 eV of Sn 3d 5/2 for Sn 4+ , Sn 2+ , and Sn 0 , respectively, and 495.15, 494.50, and 493.10 eV of Sn 3d 3/2 for Sn 4+ , Sn 2+ , and Sn 0 , respectively, indicating metallic Sn existing in SFO@C-III. 28 Figure 3d shows the C 1s XPS spectrum of SFO@C-IV; other samples are shown in Figure S10. The peaks at 284.80, 286.19, and 288.52 eV are related to C−C, C−O, and CO/ O−CO bonds, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Originating from the low interfacial tension and high permeability brought by the poloxamer surfactant, the wettability between Zn foil and Polo-ZnSO 4 is significantly enhanced (Figure S18) compared to the ZnSO 4 electrolyte, which is beneficial to reducing the contact impedance (335.4 Ω to 130.0 Ω, Figure S19 and Table S3) and enhance the electrode reaction efficiency. , Moreover, the ionic conductivity (Figure S20) shows that the addition of the poloxamer has little effect on the transport of zinc ions. As demonstrated by optical photographs (Figures a and S21) and surface SEM (Figures b and S22 ), zinc dendrites (pink line) are easily grown in ZnSO 4 electrolytes under continuous deposition of 5 mA cm –2 .…”
Section: Surface Morphology Of the Sei On The Zn Anodementioning
confidence: 99%